The Success of Student Scientific Publications: Case Study of Islamic Higher Education in Indonesia - Hidayatul Fikra; Wahyudin Darmalaksana (STAI Hubbulwathan Duri, 2022)
Students interested in Islamic scholarship face tremendous challenges in achieving scientific publications. Based on these backgrounds and problems, this study aims to discuss the success of the management of scientific publications of students interested in Islamic scholarship in Islamic higher education in Indonesia. This research applies a qualitative type with a participatory method and a SOAR analysis approach. The results and discussion of this study indicate that students who are interested in Islamic scholarship experience effectiveness in publication in scientific journals through strategic planning, governance, and strengthening the capacity of writing scientific articles. This study concludes that good management includes participation based on stakeholder aspirations, strengthening of writing trainer resources, professionalism, curriculum objectives, and support systems, so that good achievements are produced as shown by students interested in Islamic scholarship in facing the challenges of publishing articles in scientific journals. This study recommends the urgency of managing scientific publications more adequately for students interested in Islamic scholarship by administrators of Islamic higher education in Indonesia.